Superiority of Microencapsulated Essential Oils Compared With Common Essential Oils and Antibiotics: Effects on the Intestinal Health and Gut Microbiota of Weaning Piglet - Mo, Kaibin; Li, Jing; Liu, Fenfen; Xu, Ying; Huang, Xianhui; Ni, Hengjia (Frontiers in Nutrition, 2022)
Essential oils (EOs) have long been considered an alternative to antibiotics in the breeding industry. However, they are unstable and often present unpleasant odors, which hampers their application. Microencapsulation can protect the active gradients from oxidation and allow them to diffuse slowly in the gastrointestinal tract. The purpose of this study was to investigate the effect of microencapsulation technology on the biological function of EOs and the possibility of using microencapsulate EOs (MEEOs) as an alternative to antibiotics in weaning piglets. First, we prepared MEEOs and common EOs both containing 2% thymol, 5% carvacrol and 3% cinnamaldehyde (w/w/w). Then, a total of forty-eight weaning piglets were randomly allotted to six dietary treatments: (1) basal diet; (2) 75 mg/kg chlortetracycline; (3) 100 mg/kg common EOs; (4) 500 mg/kg common EOs; (5) 100 mg/kg MEEOs; and (6) 500 mg/kg MEEO. The trial lasted 28 days. The results showed that piglets in the100 mg/kg MEEOs group had the lowest diarrhea index during days 15-28 (P < 0.05). In addition, 100 mg/kg MEEOs significantly alleviated intestinal oxidative stress and inflammation (P < 0.05), whereas 500 mg/kg common EOs caused intestinal oxidative stress (P < 0.05) and may lead to intestinal damage through activation of inflammatory cytokine response. MEEOs (100 mg/kg) significantly reduced the ratio of the relative abundance of potential pathogenic and beneficial bacteria in the cecum and colon (P < 0.05), thus contributing to the maintenance of intestinal health. On the other hand, chlortetracycline caused an increase in the ratio of the relative abundance of potential pathogenic and beneficial bacteria in the colon (P < 0.05), which could potentially have adverse effects on the intestine. The addition of a high dose of MEEOs may have adverse effects on the intestine and may lead to diarrhea by increasing the level of colonic acetic acid (P < 0.05). Collectively, the results suggest that microencapsulation technology significantly promotes the positive effect of EOs on the intestinal health of weaning piglets and reduces the adverse effect of EOs, and 100 mg/kg MEEOs are recommended as a health promoter in piglets during the weaning period.